Transferring Culture in Translations — Modern and Postmodern Options - Müller, Klaus (TTR, 1995)
AbstractTransferring Culture in Translations - Modern and Postmodern Options — The characteristic elements of the modern theories of translation by Charles Baudelaire and Sigmund Freud are outlined and described in the context of the question of how differences in culture and understanding can be recognized and translated. Translations depend on a certain homogeneity (between the different sign systems used) which can be provided by the creation of meaning through language. The understanding, acknowledgement and creation of meaning is vital for translations. Both Baudelaire and Freud are quite aware of the relative value of such meaning. In postmodernist theories, translation becomes 'necessarily impossible.' Paul de Man's and Jacques Derrida's practical use of Walter Benjamin's text on translation indeed shows that they do not translate him. They do, however, adapt him to their own view and their specific meaning. More and different meanings can be detected in Benjamin, though, and the necessity for multiple, ambiguous, but not entirely arbitrary translations must be recognized. Only a meaningful, inventive combination of one's own and the other's positions can make cultural transfer and the acknowledgement and tentative understanding of otherness possible.